Episodes of Reentry Type Biopotentials exited in Isolated Atrium by Competing Sources - Skučas, M.; Grigaliūnienė, I.; Labrencas, R. (Elektronika ir Elektrotechnika, 2005)
This paper presents the investigation of excitation possibilities for a reentry type biopotentials in atrium by the imitation of ectopic sources. The experiment was processed on isolated atrium of a rabbit. Parasystolic arrhythmias were provoked by couple of electrostimulators periodical stimulation. The periods of stimulus were T1=398 ms and T2=450 ms. There was recorded an appearance of the short-term 45 episodes of reentry type action potentials in atrium cells under these conditions. The experimental data confirms the significance of ectopic sources for the existence of reentry type biopotencials. We observe period decrease by four times at the reentry appearance time, compared with stimulation periods. We identified, that one of the reasons for the appearance of reentry episodes can be the stimulus of the other excitation source, if it is an obstacle for a wave of first excitation source and if it chances the direction of the first source wave, which leads to a spiral wave forming. Ill. 3, bibl. 12 (in Lithuanian; summaries in Lithuanian, English and Russian).